Phenylarsonic Acid Compounds with Broad-Spectrum and Potent Cytotoxic Activity against Human Cancer Cells - Uckun, Fatih M.; D’Cruz, Osmond J.; Liu, Xing-Ping; Narla, Rama Krishna (Arzneimittelforschung, 2003)
The in vitro cytotoxic activity profile of nine novel phenylarsonic acid (CAS 98-05-5, PAA) compounds against 17 human cancer cell lines including (a) ovarian cancer cell lines ES-2, PA-1, CAOV-3, OVCAR-3, (b) testicular cancer cell lines Ntera-2, Tera-2, N2NICP, 833K, and 64CP, (c) multiple myeloma cell lines ARH77, HS-Sultan, RPMI-8226, and U266, and (d) acute lymphoblastic leukemia (ALL) cell lines NALM-6, MOLT-3, ALL-1, and RS4; 11, was determined by the MTT assay. The lead compounds, 2-methylthio-4-[(4’-aminophenylazo)-phenylarsonic acid] pyrimidine (PHI-370) and 2-methylthio-4-(4’-phenylarsonic acid)-aminopyrimidine (PHI-380) caused apoptotic death in all 17 cancer cell lines at low micromolar concentrations, as documented by TUNEL assays and confocal laser scanning microscopy. PHI-380 was also tested and found to be very active against primary tumor cells isolated from surgical biopsy specimens of 14 patients with therapy-refractory non-small cell lung cancer, breast cancer, colon cancer, lymphoma, hepatoblastoma, or Wilm’s tumor as well. Because of their broad-spectrum and potent anticancer activity and ability to induce apoptosis in primary tumor cells from therapy-refractory cancer patients, PAA compounds such as PHI-370 and PHI-380 may provide the basis for effective salvage regimens for patients with recurrent cancer.
Keywords: Anticancer agents, broadspectrum; CAS 98-05-5; Organic arsenicals; Phenylarsonic acid derivatives, apoptosis, cytotoxicity